INDONESIAN RURAL DEVELOPMENT AT CROSSROAD: INSTITUTIONAL REFORM, LOCAL ECONOMIC DEVELOPMENT AND APPLIED TECHNOLOGY - Anggun Trisnanto Hari Susilo; Budi Waluyo; Susinggih Wijana; Merlya Balbeid; Mahmuddin Ridlo; Danniary Ismail Faronny (UNIVERSITAS PAKUAN, 2021)
The Indonesian Government releases the Law 6/2014 on Village. Since then, there are lively discussions about its implementation. In its 7th years of implementation, this paper intends to analyse on how and to what extent the implementation of the Village Law has determined village development in Indonesia. This paper is based on case study approach, which is conducted in seven selected villages in East Java Province. Data is collected by series of interviews with village heads, member of village council, women and youth representatives. This paper presents that there are three main popular sectors of village development in Indonesia namely institutional reform, local economic development and applied technology. On this, the paper argues that applied technology is less problematic than the other two. Institutional reform and local economic development are two sector that many problems (social and political) are identified. This relates to existing social-political structures of traditional Javanese village as well as problem of capacity.